1983
DOI: 10.1093/ajcp/80.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Sheep Erythrocyte Rosette Formation by B Chronic Lymphocytic Leukemia Cells as a Consequence of Monoclonal Surface Immunoglobulin with “Forssman-like” Antibody Activity

Abstract: Peripheral blood and splenic lymphocytes from an elderly man with chronic lymphocytic leukemia (Rai stage 4) were shown to have monoclonal surface immunoglobulin (IgM+, IgD+, kappa+), Ia-like antigen and receptors for unsensitized sheep red blood cells. The sheep red blood cell receptor was not blocked by monoclonal antibodies that bind to the classic T lymphocyte rosette receptor (OKT-11 and Lyt-3) or by anti-human IgG or antilambda antibodies. However, the sheep red blood cell receptor was blocked by antihum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other human B-CLLs form rosettes with SRBC via their cell-surface immunoglobulins. We have recently been able to demonstrate that a B-CLL which forms rosettes with untreated SRBC (Deegan et al 1983) also forms rosettes with BrMRBC and binds PC in synthetic liposomes (Mercolino, Deegan, Arnold and Haughton, in preparation). The similar chemical structures recognized by B cells of the Ly-1/Leu-1 lineage suggests that defective idiotypic regulation may be implicated in their over-representation in B cell neoplasia and their common association with autoimmune phenomena.…”
Section: Antigen Specificity Of Ch Lymphoma Immunoglobulinsmentioning
confidence: 99%
“…Other human B-CLLs form rosettes with SRBC via their cell-surface immunoglobulins. We have recently been able to demonstrate that a B-CLL which forms rosettes with untreated SRBC (Deegan et al 1983) also forms rosettes with BrMRBC and binds PC in synthetic liposomes (Mercolino, Deegan, Arnold and Haughton, in preparation). The similar chemical structures recognized by B cells of the Ly-1/Leu-1 lineage suggests that defective idiotypic regulation may be implicated in their over-representation in B cell neoplasia and their common association with autoimmune phenomena.…”
Section: Antigen Specificity Of Ch Lymphoma Immunoglobulinsmentioning
confidence: 99%
“…Using this technique no accurate information on T-cell subpopulations is obtained because of variation in affinity during E-rosette formation, limited purity or enriched T cell and selective loss of T-cell subpopulations by enrichment [21]. Further complications arise from E-rosette formation by immunoglobulin positive cells [22] and presence of E receptors in B-CLL cells [23]. To our knowledge only three studies have been reported in which direct assessment of T-cell subpopulations in B-CLL is per-formed [2,5,8].…”
Section: Discussionmentioning
confidence: 99%